Comparative study of Single Crystal (SC)-Diamond and 4H-SiC bulk radiation detectors for room temperature alpha spectroscopy. (21st June 2021) - Mohapatra, S.; Abhangi, M.; Vala, S.; Kumar Sahu, P.; Rath, S.; Narasimha Murty, N.V.L.
Abstract: In this work, the fabrication, electrical characterization and alpha spectral characterization of single-crystal (SC) diamond bulk radiation detector have been carried out. The performance metrics of the SC-diamond bulk detector such as the leakage current density, charge collection efficiency, spectral resolution and polarization effects are studied and are compared with a bulk detector fabricated using High-Pure Semi-Insulating (HPSI) 4H-SiC. It is found that the SC-diamond detector exhibits lower leakage current density, higher μτ product, better spectral resolution and no polarization effects in comparison to the HPSI 4H-SiC detector. The time response analysis of the SC-diamond detector is carried out to study the effect of alpha particles on the operation of the SC-diamond detector. Accordingly, the stability of the SC-diamond detector is tested by evaluating the total counts versus real time and the performance of the diamond detector is found to be stable during the alpha-time spectroscopy. Hence, diamond bulk detectors using commercially available electronic grade diamond may be better suited for alpha particle spectroscopy compared to HPSI 4H-SiC of nearly equivalent thickness.